The interaction of the oxytocin receptor gene and child abuse subtypes on social cognition in euthymic patients with bipolar disorder type I - Ríos, Ulises; Morán, Javier; Hermosilla, Jimena; González, René; Muñoz, Paulina; Arancibia, Marcelo; Herrera, Luisa; Jiménez, Juan Pablo; Moya, Pablo R. (Frontiers in Psychiatry, 2023)
Most studies on cognitive impairment in bipolar disorder have neglected the role of early stress, despite the high frequency of childhood maltreatment in this clinical group. The aim of this study was to establish a connection between a history of emotional, physical, and sexual abuse in childhood and social cognition (SC) in patients with bipolar disorder type I (BD-I) in euthymia, and to test a possible moderating effect of the single nucleotide polymorphism rs53576 in the oxytocin receptor gene (OXTR). 101 participants were included in this study. History of child abuse was evaluated using the Childhood Trauma Questionnaire–Short Form. Cognitive functioning was appraised using The Awareness of Social Inference Test (social cognition). The interaction effect between the independent variables OXTR rs53576 (AA/AG and GG) and the absence or presence of any one type of child maltreatment or a combination of types was analyzed using a generalized linear model regression. BD-I patients who had been victims of physical and emotional abuse in childhood and were carriers of the GG genotype at OXTR rs53576 displayed greater SC alterations, specifically in emotion recognition. This gene-environment interaction finding suggests a differential susceptibility model of a genetic variants that can be plausibly associated with SC functioning and might help to identify at-risk clinical subgroups within a diagnostic category. Future research aimed at testing the interlevel impact of early stress constitutes an ethical-clinical duty given the high rates of childhood maltreatment reported in BD-I patients.